2020
DOI: 10.1371/journal.pone.0232034
|View full text |Cite
|
Sign up to set email alerts
|

A summary of bird mortality at photovoltaic utility scale solar facilities in the Southwestern U.S.

Abstract: Recent trends in renewable energy development in the United States (U.S.) show that new installed capacity of utility-scale solar energy has exceeded 30% of total installed capacity of all sources per year since 2013. Photovoltaic solar energy provides benefits in that no emissions are produced; however, there are potential impacts from photovoltaic solar development on birds that include habitat loss and potential for collision mortality. Only 2 papers in the peer-reviewed literature present fatality informat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 20 publications
1
32
1
Order By: Relevance
“…Aquatic insects can also be attracted to the polarised light reflected by PV panels, and display maladaptive behaviour mistaking the panels for water surfaces. 85 Kosciuch et al (2020). Kagan et al (2014).…”
Section: Operationmentioning
confidence: 99%
“…Aquatic insects can also be attracted to the polarised light reflected by PV panels, and display maladaptive behaviour mistaking the panels for water surfaces. 85 Kosciuch et al (2020). Kagan et al (2014).…”
Section: Operationmentioning
confidence: 99%
“…In a summary of bird carcasses that were opportunistically obtained from three USSE solar facilities (two concentrating solar power and one PV) in California, U.S., Kagan et al [3] determined that 48% (27/56) of identifiable remains found at the Desert Sunlight PV USSE facility (hereafter Desert Sunlight) in California, U.S., were of aquatic habitat birds that foraged in water. The carcasses from Desert Sunlight included species that rely on water for takeoff and landing (e.g., family Gaviidae) and those that use water for some aspect of their life history (e.g., family Charadriidae); these groups are defined by Kosciuch et al [4] as water obligates and water associates, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Further, as the LEH was developed based on one PV USSE facility, it was unknown whether the occurrence of aquatic habitat birds was unique to Desert Sunlight or whether the pattern was widespread among PV USSE facilities in southern California, U.S. In a summary of 13 studies at 10 PV USSE facilities in the Southwestern U.S., Kosciuch et al [4] determined that carcasses of water-obligate birds were documented in 90% (9/10) of studies in the Sonoran and Mojave Desert (SMD) Bird Conservation Region (BCR), the region where Desert Sunlight is located. However, Kosciuch et al [4] found that water obligates were detected in only one of three studies outside the SMD BCR.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations